Amphiphilic Anionic Oligomer-Stabilized Calcium Phosphate Nanoparticles with Prospects in siRNA Delivery via Convection-Enhanced Delivery - Franziska Mitrach; Maximilian Schmid; Magali Toussaint; Sladjana Dukic-Stefanovic; Winnie Deuther-Conrad; Heike Franke; Alexander Ewe; Achim Aigner; Christian Wölk; Peter Brust; Michael C. Hacker; Michaela Schulz-Siegmund (Pharmaceutics, 2022)
Convection-enhanced delivery (CED) has been introduced as a concept in cancer treatment to generate high local concentrations of anticancer therapeutics and overcome the limited diffusional distribution, e.g., in the brain. RNA interference provides interesting therapeutic options to fight cancer cells but requires nanoparticulate (NP) carriers with a size below 100 nm as well as a low zeta potential for CED application. In this study, we investigated calcium phosphate NPs (CaP-NPs) as siRNA carriers for CED application. Since CaP-NPs tend to aggregate, we introduced a new terpolymer (o14PEGMA(1:1:2.5) NH3) for stabilization of CaP-NPs intended for delivery of siRNA to brain cancer cells. This small terpolymer provides PEG chains for steric stabilization, and a fat alcohol to improve interfacial activity, as well as maleic anhydrides that allow for both labeling and high affinity to Ca(II) in the hydrolyzed state. In a systematic approach, we varied the Ca/P ratio as well as the terpolymer concentration and successfully stabilized NPs with the desired properties. Labeling of the terpolymer with the fluorescent dye Cy5 revealed the terpolymer’s high affinity to CaP. Importantly, we also determined a high efficiency of siRNA binding to the NPs that caused very effective survivin siRNA silencing in F98 rat brain cancer cells. Cytotoxicity investigations with a standard cell line resulted in minor and transient effects; no adverse effects were observed in organotypic brain slice cultures. However, more specific cytotoxicity investigations are required. This study provides a systematic and mechanistic analysis characterizing the effects of the first oligomer of a new class of stabilizers for siRNA-loaded CaP-NPs.